2011
DOI: 10.1089/hum.2010.045
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow as a Source of Hematopoietic Stem Cells for Human Gene Therapy of β-Thalassemia

Abstract: β-Thalassemia is a severe inherited anemia caused by insufficient production of β-globin chains. Allogeneic hematopoietic stem cell (HSC) transplantation is currently the only cure, and is limited by donor availability and regimen-related toxicity and mortality. Gene therapy is a promising therapeutic tool for all thalassemic patients lacking a compatible donor and potentially provides transfusion independence in the absence of transplant-related complications, such as graft rejection and graft-versus-host dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…Frittoli et al reported that bone marrow aspirated from human iliac crest contains *10-20 million BMNCs per mL. 31 Therefore, 10 mL of bone marrow aspirate is sufficient to construct a 10 cm graft with a 5 mm internal diameter according to the cell seeding density in the present study. Obtaining 10 mL bone marrow aspirates from human is highly feasible.…”
Section: Discussionmentioning
confidence: 60%
“…Frittoli et al reported that bone marrow aspirated from human iliac crest contains *10-20 million BMNCs per mL. 31 Therefore, 10 mL of bone marrow aspirate is sufficient to construct a 10 cm graft with a 5 mm internal diameter according to the cell seeding density in the present study. Obtaining 10 mL bone marrow aspirates from human is highly feasible.…”
Section: Discussionmentioning
confidence: 60%
“…Splenic enlargement and rupture in healthy donors has been reported after administration of G‐CSF . This risk needs to be assessed in patients with β‐thalassemia and other hemoglobinopathies, since some of the patients have splenomegaly before G‐CSF administration . G‐CSF also increases the risk of thrombotic events in otherwise healthy donors due to coagulation and endothelial cell activation related to G‐CSF .…”
Section: Discussionmentioning
confidence: 99%
“…4 More recent developments in genetic therapy have led to the collection of autologous stem cells, which are then genetically corrected and reinfused to the patient to treat hemoglobinopathies. 5 Additionally, improved treatment modalities in this patient population have resulted in extended life spans but with a concomitant increased incidence of hematologic malignancies. 6-10 A recent case report featured a patient with Hb SC disease who underwent an autologous stem cell transplant for MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 In a clinical case report, peripheral blood marking levels were initially low before a single clone expanded and eventually compensated for overall low transduction efficiency. 24 Here, we demonstrate for the first time that we can achieve globin gene transfer in thalassemic G-CSF mobilized HPCs in the range of 0.4 to 0.6 VC/cell under cGMP conditions.…”
mentioning
confidence: 99%